1985
DOI: 10.1302/0301-620x.67b3.3997957
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of subacute osteomyelitis in childhood

Abstract: A protocol for the treatment of subacute haematogenous osteomyelitis has been used and evaluated in 71 children. A group of 26 children with a radiologically "aggressive" lesion had biopsy followed by antibiotics and immobilisation for six weeks. A group of 45 children with 48 cavities in the metaphysis or the epiphysis or both was further subdivided according to the presence or absence of clinical signs of pus at subperiosteal level or in a joint. Children with evidence of pus had operation followed by antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
1
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 10 publications
4
63
1
2
Order By: Relevance
“…However, it has been reported that healing with radiological changes takes place over 6-12 months. 1 Our patient was clinically well at the six-month, one-and two-year follow-up visits with no leg length discrepancy seen. Further radiological investigation was therefore deemed unnecessary.…”
Section: Surgical Techniquesupporting
confidence: 50%
See 1 more Smart Citation
“…However, it has been reported that healing with radiological changes takes place over 6-12 months. 1 Our patient was clinically well at the six-month, one-and two-year follow-up visits with no leg length discrepancy seen. Further radiological investigation was therefore deemed unnecessary.…”
Section: Surgical Techniquesupporting
confidence: 50%
“…6 Ross and Cole reported 24 cases with both metaphyseal and epiphyseal lesions. 1 Initial curettage with six weeks of antibiotics was performed in four cases, for formation of subperiosteal pus, extension into the adjacent joint or diagnostic purpose. Of the 20 treated conservatively with 6 weeks of antibiotics, 2 had late surgical curettage for failure to respond to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Metaphyseal lesions are the most common and occur mainly in the tibia. 1,2,4,6,7,13 Type 1a is a punched-out localised zone of lucency and can mimic forms of histiocytosis especially an eosinophilic granuloma. Type 1b resembles a typical Brodie's abscess with dense sclerotic margins and may be mistaken for an osteoid osteoma.…”
Section: Discussionmentioning
confidence: 99%
“…20 There have been several recent reports of the epiphyseal form of the condition (type V) which, however, remains rare. 2,6,13,16,21 The lesions appear as a central lucency, with a faint sclerotic margin and may resemble a chondroblastoma. They usually occur within the epiphysis in children less than six years old and do not cross the epiphyseal plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation